Wirausaha Santri Berbasis Budidaya Tanaman Hidroponik - Izzuddin, Ahmad (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2016)
Cultivation of hydroponic plants need to be socialized in detail and depth to the students Ponpes Life Skill DaarunNajaah. In addition to training students to grow plants that are effective and efficient, training hydroponic plant cultivation is expected to train the spirit of independence and entrepreneurial spirit in view of this hydroponic plant is a plant that has the potential to sell on the market because the quality is good for health. Farming with hydroponics system saves 90% of water use compared with planting in the ground. Hydroponics system has many advantages than conventional systems with their land.